Flemish students' historical reference knowledge and narratives of the Belgian national past at the end of secondary education (UCL Press, 2017)
Since the early nineteenth century, western governments have expected history education to play a vital role in the formation of a national identity and the pursuit of national cohesion, by fostering shared knowledge and a shared (master)narrative of the national past. This article reports on a qualitative study that examines which narratives young adults construct about their national past, to what extent those narratives are underpinned by existing narrative templates, whether they reflect on the fact that the national past can be narrated in different ways, and to what extent they share a common reference knowledge. The study addresses the Flemish region of Belgium, a case characterized by a specific context of a nation state in decline, wherein diverse and often conflicting historical narratives coexist in popular historical culture and where the national past is almost absent from history education. A total of 107 first-year undergraduate history students were asked to write an essay on how they saw the national past. The influence of both history education and popular historical culture was reflected in the reference knowledge as well as in the (absence of) templates that students used to build their essays. Templates were not critically deconstructed, although some students nevertheless were able to discern and criticize existing 'myths' in the national past.